2017
DOI: 10.1016/j.applthermaleng.2016.11.109
|View full text |Cite
|
Sign up to set email alerts
|

Pd enhanced WC catalyst to promote heterogeneous methane combustion

Abstract: Within this work, a MgO stabilized ZrO2 (MSZ) porous media with and without a gadolinia doped ceria (Ce0.8Gd0.2O1.9, GDC) catalyst coating has been evaluated in heterogeneous combustion of mixtures of methane and air at different equivalence ratios inside of a porous combustor. The temperature distribution within the combustion chamber along with optical and acoustic emissions profiles from the exhaust side of the combustion chamber have been analyzed to characterize performance of the combustor. It was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…It has also been considered as a replacement for Ir systems in satellite thrusters powered by hydrazine [ 42 ]. Pd enhanced WC catalyst was used successfully in heterogeneous methane combustion [ 43 ]. Composite materials contain Pd(0) and W 2 C particles well-dispersed on carbon were investigated as hydrogen evolution catalysis [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been considered as a replacement for Ir systems in satellite thrusters powered by hydrazine [ 42 ]. Pd enhanced WC catalyst was used successfully in heterogeneous methane combustion [ 43 ]. Composite materials contain Pd(0) and W 2 C particles well-dispersed on carbon were investigated as hydrogen evolution catalysis [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been shown that combustion instabilities have a wave-like component, acoustic emission profiles were a focus of this study. In addition to the measurement of acoustic emissions, temperature profiles at fixed locations within the combustion chamber and radiative emissions in the visible spectrum from the exhaust were collected from the combustion chamber, while operation was conducted at various equivalence ratios and a fixed air flow rate, using methane as fuel.When such a study is conducted, the optimal porous media for given ranges of equivalence ratios may be determined and evaluated as potential substrates for catalytic applications. …”
Section: Introductionmentioning
confidence: 99%